Clinical Characteristics of Secondary Immune Thrombocytopenia Associated With Primary Sjögren's Syndrome - Dai, Fan; Yang, Guomei; Rao, Peishi; Wu, Puqi; Chen, Rongjuan; Sun, Yuechi; Peng, Yun; Qian, Hongyan; Wang, Bin; Chen, Shiju; Liu, Yuan; Shi, Guixiu (Frontiers in Medicine, 2020)
Objective: Clinical characteristics of immune thrombocytopenia (ITP) associated with primary Sjögren's syndrome (pSS) have not been clearly defined. This study aimed to evaluate the prevalence and clinical characteristics of secondary ITP in patients with pSS. Methods: 291 pSS patients in our hospital were retrospectively analyzed. Clinical manifestations and laboratory findings were compared between pSS patients with and without ITP. Results: The prevalence of secondary ITP in pSS patients was 12.03%. Compared to pSS patients without ITP, pSS patients with ITP were younger and had higher disease activity. The prevalence of interstitial lung diseases (ILD) was significantly lower in pSS patients with ITP (30.43 vs. 54.95%; P = 0.029), and it was the same with arthritis (17.14 vs. 3.9.11%; P = 0.014) and dry eye (33.33 vs. 54.17%, P = 0.027) compared with those without ITP. Serum creatinine level was lower in pSS patients with ITP (P = 0.009), while positivity of anti-histone autoantibodies was higher in pSS patients with ITP (P = 0.025). Conclusion: This study is an initial report describing clinical features of ITP in pSS. The lower incidence of ILD and arthritis among pSS patients with ITP indicated potential active roles of platelets in the pathogenesis of fibrosis or inflammatory arthritis, which may open the way for further experimental and clinical work.